PERAN APOTEKER DALAM PEREDARAN OBAT SECARA DARING DI PRAKTIK KEFARMASIAN DI PURWOREJO - Aminudin; Merari Peranginangin, Jason; Herdwiani, Wiwin (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Online drug distribution are one of the essential elements to realize health in health administration. The Food and Drug Monitoring Agency (BPOM) has provided and disseminated Regulation 8 of 2020 concerning the Control of Drugs and Food Circulated Online. This study aims to determine the role of pharmacists in online drug distribution in pharmaceutical practice. Sampling was done by purposive sampling with interviews. Informants in this study include pharmacists who practice in pharmacies that already serve online drug sales, furthermore, the data is processed with NVIVO 12 Pro software. The study results show that pharmacists' role in online drug distribution is to serve incoming drug requests, ensure the availability of quality drugs, ensure that these requests comply with applicable regulations, and ensure that the drugs reach patients safely